Relevant, less relevant and irrelevant isokinetic strength test parameters: Some critical comments - Dvir, Z. (Movement & Sport Sciences - Science & Motricité, 2014)
Isokinetic dynamometry is now widely recognized as the standard tool for assessing muscle performance. However there is still quite a diversity in terms of the report document that is produced following the test/s reflecting various approaches taken by the manufacturers of these instruments. Of particular significance is the use of outcome parameters i.e. those 'numbers' according to which, interpretation regarding muscle performance level may be judged. It appears that some of the parameters that became mainstays of isokinetic reports are redundant at best and misleading, at worst. This short paper is not intended to be a comprehensive review of all outcome parameters but a commentary that sheds light on the main issues concerning this topic.